Influence of intertidal seascape on the functional structure of fish assemblages: Implications for habitat conservation in estuarine ecosystems. Issue 4 (31st May 2018) - Teichert, Nils; Carassou, Laure; Sahraoui, Yohan; Lobry, Jérémy; Lepage, Mario
Abstract: Habitat loss and fragmentation remain major threats in estuaries, particularly with respect to the erosion of intertidal areas that provide shelter and food resources for numerous fish species. Improving our understanding of the fauna–intertidal seascape relationship is thus of critical importance. Here, the seascapes of 24 tidal estuaries were compared at multiple spatial scales (from estuary to local) to determine how the spatial structure of intertidal patches affects the abundance of several fish functional groups. For the majority of fish groups, our results support the statement that a large intertidal area can support high fish abundance at both of the studied scales; however, the spatial distribution of patches within estuaries, and especially the presence of large intertidal patches close to the estuary mouth, appeared to be an important feature for both marine and estuarine‐resident fish. It was also shown that habitat fragmentation at the estuary scale is associated with a decline in the abundance of several fish groups, probably as a result of reduced intertidal suitability and accessibility. At the local scale, the area of intertidal–subtidal interface was positively related to fish densities, emphasizing the importance of fish having permanently flooded refuges close to feeding grounds. This study provides essential insights to guide conservation and restoration actions for intertidal areas at both estuary and local scales (10–100 m 2 ), by stressing differences in species sensitivity to seascape modification.